An assessment of the relationship between democracy and economic growth: a case study of Zimbabwe from 1980 - 2008 - Devera, , Tawanda (Midlands State University, 2019)
This research was conducted to assess the relationship that exist between democracy and economic growth, examining whether the two have an effect on each other, that is, does democracy foster or it actually hinders economic growth and also if economic growth influence a nation to be a democratic or to a be a non-democratic one. Thus the essence of the study is to investigate the robustness of the relationship. Zimbabwe was used as the case study to help out in the conduction of this research. The research appealed to secondary information as its own very source of data thus the data used to reach a conclusion pertaining to the objective of this research was derived from journals, books, government and non-governmental reports and internet sources. The results gained after the analysis of that data reveal that there is a relationship between the two variables, though the relationship cannot be said that it is that of close proximity. As the research was conducted using Zimbabwe as the case study, it wrapped up the study by giving recommendations linked to the nation used as the case study which sought to address problems which arose from the breakdown of the relationship and those which also affected the linkage of the two variables leaving the country bearing the undesirable consequences.